An initial examination of state and longitudinal effects of loving-kindness practice on affective and motivational states at work - MASTERS-WAAGE, Theodore Charles (Institutional Knowledge at Singapore Management University, 2021)
Objectives: Drawing on practices and concepts from Buddhist ethics, we developed a loving-kindness training. We investigated the state and longitudinal effects of this training on employees’ affective and motivational states at work in two studies. Methods: Study 1 tested this training program in a randomized controlled trial, comparing the effects of loving-kindness practice on employee affect and motivation with an active (mindfulness) and a passive (waitlist) control condition. Analyses focused on both longitudinal effects (increases in affect and motivation over the training period) and state effects (effects of practice on daily affect and motivation). Study 2 conducted a 1-week study to further probe the state effects of loving-kindness and the effectiveness of formal vs. informal practice. Results: Results indicated mixed support for longitudinal effects, with individuals in the loving-kindness condition showing increases in work motivation, affective valence, and activation over time but the majority of these increases not being statistically different from trends in the two control conditions. Analysis of state (day-level) effects found consistent support for a beneficial effect of loving-kindness practice on daily affective valence and motivation. Analyses from study 2 replicated these day-level effects and provided evidence for the efficacy of both formal and informal practice-based training programs. Conclusions: This research provides initial support for the potential benefits of loving-kindness practice in a workplace context. We discuss theoretical and practical implications including the future of loving-kindness practice as a workplace training intervention.